EFFECTIVENESS OF 5% GUAVA LEAF (Psidium guajava Linn) EXTRACT OF WHITE FRUIT VARIANT TO DECREASE LEVELS OF Volatile Sulfur Compounds (VSCs) IN HALITOSIS SUFFERERS - Melina Vania Elian; Nuzulia Irawati; Surya Nelis (Faculty of Dentistry Universitas Andalas, 2013)
Halitosis is a general term used to describe the bad breath coming out of the oral cavity. Volatile Sulfur Compounds (VSCs) are a major component causes of halitosis, formed from the break down of protein substrate by gram-negative anaerobes such as Porphyromonas gingivalis, Tanerella forsythia, Fusobacterium nucleatum, Prevotella intermedia and Treponema denticola. Guava leaf (Psidium guajava Linn) contain high levels of quercetin compounds that can inhibit the growth of Porphyromonas gingivalis and Prevotella intermedia. This study aims to determine the effectiveness of 5% guava leaf (Psidium guajava linn) extract of white fruit variant to decrease levels of Volatile Sulfur Compounds (VSCs) in halitosis sufferers. This research method was pre-experimental which consists of 19 subjects. The guava leaf (Psidium guajava Linn) extract was made by maceration method and diluted with distiled water at 5% concentration. The levels of Volatile Sulfur Compounds (VSCs) were measured by breath checker before (pre test) and after (post test) treatment. Wilcoxon test showed that there was a significant difference between the levels of Volatile Sulfur Compounds (VSCs) before and after gargling with 5% guava leaf (Psidium guajava Linn) extract of white fruit variant (p<0,05). The conclusion of this research was 5% guava leaf (Psidium guajava Linn) extract of white fruit variant effectively decreases levels of Volatile Sulfur Compounds (VSCs) in halitosis sufferers.